Expert Consensus on the Application of Ulinastatin in Common Clinical Critical Illness - Expert group of expert consensus on the application of ulinastatin in common clinical critical illness (Zhongguo quanke yixue, 2023)
Ulinastatin is mainly applied in the treatment of acute pancreatitis, but also in other common clinical critical illnesses such as shock, sepsis, evere pneumonia, cute respiratory distress syndrome, several acute poisoning, severe heat stroke, severe burns, severe trauma, and patients with sudden cardiac arrest for its roles in proteolytic enzymes inhibition and inflammatory responses regulation, which has been recommended by several guidelines/expert consensus on the diagnose and treatment of common clinical critical illness. However, there is currently a lack of consensus on the rational use of ulinastatin in terms of indications, usage, dosage, and others. Therefore, in order to promote the standardized application of ulinastatin, the expert group of expert consensus on the application of ulinastatin in common clinical critical illness summarized the mechanism, pharmacokinetics, indications of ulinastatin and its application methods in the treatment of common clinical critical illness, in order to provide a reference for the rational application of ulinastatin in clinical practice.